Liquid Crystals Self-Organized Soft Functional Materials for Advanced Applications - Carlescu, Irina (IntechOpen, 2019)
Liquid Crystals - Self-Organized Soft Functional Materials for Advanced Applications is focused on both theoretical models and experimental results, pointing out the chemical and physical properties (thermodynamics, electro-optic switching behavior, and non-linear optic phenomena) of liquid crystals used in a wide range of devices. In this respect, the chapters cover the following topics: chemical structure and phase transitions in bent-core liquid crystals, phase and structural behavior of liquid crystals used to align carbon nanotubes, molecular alignment, and photorefractive effect in the ferroelectric phase, which has the potential to be used as transistors, for image storage, and in optical signal processing. It is expected that the book will be of interest to researchers in academia and industries, as well as advanced students.